2014
DOI: 10.1371/journal.pone.0111820
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Expression Analysis of MicroRNAs in the Tube Foot of Sea Cucumber Apostichopus japonicus

Abstract: MicroRNAs (miRNAs) are a class of endogenous non-coding small RNA with average length of 22 nucleotides, participating in the post-transcriptional regulation of gene expression. In this study, we report the identification and characterization of miRNAs in the tube foot of sea cucumber (Apostichopus japonicus) by next generation sequencing with Illumina HiSeq 2000 platform. Through the bioinformatic analysis, we identified 260 conserved miRNAs and six novel miRNAs from the tube foot small RNA transcriptome. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…The most abundant miRNAs were miR-1c, miR-10, and miR-71c-5p in the LTM, while the most abundant miRNAs were miR-1c, miR-10, and miR-200-3p in the RPT. This observation was consistent with previous studies [ 9 , 10 , 12 ], in which miR-1c and miR-10 were reported to be highly expressed. Taken together, it’s clear that miR-1c and miR-10 were the top two abundant miRNAs in the various tissues of sea cucumber examined to date.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The most abundant miRNAs were miR-1c, miR-10, and miR-71c-5p in the LTM, while the most abundant miRNAs were miR-1c, miR-10, and miR-200-3p in the RPT. This observation was consistent with previous studies [ 9 , 10 , 12 ], in which miR-1c and miR-10 were reported to be highly expressed. Taken together, it’s clear that miR-1c and miR-10 were the top two abundant miRNAs in the various tissues of sea cucumber examined to date.…”
Section: Discussionsupporting
confidence: 94%
“…The small RNA length distribution showed that 20-24nt was the main length in both the LTM and RPT, which is the typical size range of miRNAs. This is consistent with other miRNA studies in echinoderm animals [ 12 , 28 30 ]. A total of 221 and 314 conserved miRNAs were identified from the RPT and LTM, of which 161 miRNAs were identified from both RPT and LTM, while 153 and 60 miRNAs were only identified from LTM and RPT, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations